1, 3, 5‐Triethynylbenzene and melamine as monomers to synthesize three‐dimensional network porous aromatic frameworks based silica/florisil for determination of carbendazim and thiabendazole in spinach. Issue 14 (25th May 2020) - Sun, Liping; Wang, Sufang; Zhu, Tao
Abstract: In this study, the new and efficient three‐dimensional network porous aromatic frameworks materials called Silica‐PAFs‐a, Florisil‐PAFs‐a, Silica‐PAFs‐b, and Florisil‐PAFs‐b were first synthesized. The properties of materials were analyzed by five characterization methods. The materials were used as adsorbents in pipette‐tip solid‐phase extraction for the effective determination of carbendazim and thiabendazole in spinach sample. Meanwhile, the obtained materials were tested by static adsorption and dynamic adsorption. The result showed that the specific surface area of materials greatly increased after introducing three‐dimensional network porous aromatic frameworks. Microstructural modification exposed a large number of amino reactive groups that made them have a better adsorption amount for the two targets. The calibration graphs of carbendazim and thiabendazole in methanol were linear over 0.10–300.0 µg/mL, and the limits of detection and quantification were 0.00546 and 0.0182 µg/mL, and 0.00741 and 0.0247µg/mL respectively. A reliable analytical method was developed for recognition targets in spinach sample by Silica‐PAFs‐b with satisfactory extraction recoveries (96.25 and 100.51%). The proposed method using the material was applied for trace analysis of the carbendazim and thiabendazole residue.